Teori dan Metodologi dalam Memahami Matan Hadis - Rizki, Muhammad; Nafi’ah, Zumma Nihayatun (Journal of Hadith Studies, 2020)
The textual interpretation of hadiths without considering their historical and contextual dimensions often leads to misunderstandings, misapplications, and even radical tendencies. This study aims to answer the following research questions: What methodologies are used in understanding the text (matan) of hadith? What interpretive approaches are employed? And how can these ensure the relevance of hadith in the development of Islamic thought? Using a qualitative library research method and descriptive-analytical approach, this study reviews classical and contemporary literature, analyzing various interpretive methods and strategies. The findings reveal three primary methodologies: analytical (tahlili), synthetic (ijmali), and comparative (muqarin), supported by three techniques—textual, contextual, and intertextual interpretations—through several approaches such as linguistic, historical, and sociological. These methodological combinations allow hadiths to be interpreted holistically and responsively to contemporary challenges. This study concludes that diverse interpretive strategies are essential in maintaining the relevance of hadith while upholding its authenticity within the dynamic landscape of modern Islamic scholarship.